Platelet Indices in Colorectal Cancer Patients with Synchronous Liver Metastases. (4th November 2019) - Li, Li; Huang, Xiao-Yi; Li, Na; Cui, Ming-ming; Wang, Rui-tao
Abstract : Aims. Liver metastases occur in approximately 25% of colorectal cancer (CRC) patients and cause more than 90% of deaths in CRC. Platelets play a crucial role in cancer progression and metastases. We aimed to investigate the relationship between platelet indices and CRC with synchronous liver metastases. Methods. We conducted a retrospective clinical study including 206 CRC patients without metastases and 200 CRC patients with synchronous liver metastases from January 1, 2015, to December 31, 2017. Data of the patients' clinicopathological characteristics were collected. Results. Platelet distribution width (PDW) was decreased in CRC patients with liver metastases compared with CRC patients without liver metastases. In addition, the prevalence of liver metastases reduced as PDW quartiles increased. After adjusting for other risk factors, the odds ratios (95% confidence intervals) for CRC liver metastases according to PDW quartiles were 1.000, 0.289 (0.156-0.535), 0.482 (0.271-0.860), and 0.190 (0.101-0.358). Conclusions. Compared with CRC patients without metastases, PDW is reduced in CRC patients with liver metastases. Moreover, PDW was independently associated with the presence of CRC liver metastases.